Hot to trot [compact disc, unabridged] - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Agatha Raisin mystery., 2020)
PI Agatha Raisin learns that her one-time lover is to be married. But the morning after the wedding, the bride is murdered. Agatha takes on the case and quickly becomes entrenched in the equestrian world.